2015
DOI: 10.1016/j.jcis.2014.10.061
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ionic concentration gradient on electroosmotic flow mixing in a microchannel

Abstract: Effects of ionic concentration gradient on electroosmotic flow (EOF) mixing of one stream of a high concentration electrolyte solution with a stream of a low concentration electrolyte solution in a micrichannel are investigated numerically. The concentration field, flow field and electric field are strongly coupled via concentration dependent zeta potential, dielectric constant and electric conductivity. The results show that the electric field and the flow velocity are nonuniform when the concentration depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 24 publications
1
24
0
2
Order By: Relevance
“…where we defined ω = KeH∇φ/ζ 2 0 as a constant which depends on external applied field ∇φ, i.e., increasing ∇φ, increases the electro-osmotic velocity and the perturbation effect on the standard potential ψ is consequently accentuated. On the other hand, increasing the distance from the wall, decreases the potential due the perturbation resulting ψ p → ζ 0 from Equation (21). Additionally, the distance between parallel plates must be greater than the distance of action of the imposed perturbation, i.e., (x − x 0 ) 2 + (y − y 0 ) 2 H. By making ψ p = ψ * p ζ 0 , x = x * H e ω = ω * H, one can write the expression for dimensionless potential: According to [41], the potential on the corners have an inverse square root of ionic concentration dependence, ψ p ∼ n −1/2 .…”
Section: Fluid Flow In a Nozzlementioning
confidence: 99%
See 1 more Smart Citation
“…where we defined ω = KeH∇φ/ζ 2 0 as a constant which depends on external applied field ∇φ, i.e., increasing ∇φ, increases the electro-osmotic velocity and the perturbation effect on the standard potential ψ is consequently accentuated. On the other hand, increasing the distance from the wall, decreases the potential due the perturbation resulting ψ p → ζ 0 from Equation (21). Additionally, the distance between parallel plates must be greater than the distance of action of the imposed perturbation, i.e., (x − x 0 ) 2 + (y − y 0 ) 2 H. By making ψ p = ψ * p ζ 0 , x = x * H e ω = ω * H, one can write the expression for dimensionless potential: According to [41], the potential on the corners have an inverse square root of ionic concentration dependence, ψ p ∼ n −1/2 .…”
Section: Fluid Flow In a Nozzlementioning
confidence: 99%
“…Afonso et al [20] demonstrated the analytical solution for viscoelastic flows in a parallel plates and circular section channel, taking into account a non-zero pressure gradient and the electrokinetic effect, where one of the constitutive models used was the simplified Phan-Thien/Thanner (sPTT). In 2015, Peng et al [21] studied the effects of a concentration gradient within a channel, taking into account a mixture of different electrolytic properties. Recently, Song et al [22] carried out studies of numerical instabilities in mixing a ferrous solution with water in a parallel walls channel.…”
Section: Introductionmentioning
confidence: 99%
“…Electrokinetic phenomena are related to the electrochemical properties of both the surface and fluid, in which the fluid motion and electrical force are interacting with each other [5,6]. One major category of these phenomena is the electro-osmotic phenomenon, in which the external electrical field causes the fluid to flow because the electrical field creases force the ions aggregated adjacent to the wall [7,8]. This kind of flow has been extensively used for transfer and mixing of fluids in microflows which are the basis for labon-a-chip devices [9].…”
Section: Introductionmentioning
confidence: 99%
“…These models are usually based on combinations of the Navier-Stokes equation for fluid flow and the Poisson-Boltzmann equation for electric potential distribution (Li et al, 2013). Amongst the applications of electro-osmotic flow are: electrokinetic treatment of contaminated soil (Cameselle, 2015, Sahoo et al 2009, electro-osmotic pumps (Li et al, 2013, Wang et al, 2009, flow mixing in microchannel (Peng and Li, 2015) and electric field-driven microreactor (Susarrey-Arce et al, 2015).…”
Section: Introductionmentioning
confidence: 99%